Exciton states in monolayer MoSe2: impact on interband transitions. (2nd November 2015) - Wang, G; Gerber, I C; Bouet, L; Lagarde, D; Balocchi, A; Vidal, M; Amand, T; Marie, X; Urbaszek, B
Abstract: We combine linear and nonlinear optical spectroscopy at 4 K with ab initio calculations to study the electronic bandstructure of MoSe2 monolayers. In one-photon photoluminescence excitation (PLE) and reflectivity we measure a separation between the A- and B-exciton emission of 220 meV, in good agreement with our calculations. In two-photon PLE we detect for the A- and B-exciton the 2p state 180 meV above the respective 1s state. In second harmonic generation (SHG) spectroscopy we record an enhancement by more than two orders of magnitude of the SHG signal at resonances of the charged exciton and the 1s and 2p neutral A- and B-exciton. Our post-density functional theory calculations show in the conduction band along the K –Γ direction a local minimum at the Λ-point that is energetically and in k -space close to the global minimum at the K-point. The influence of this local minimum on exciton transitions is discussed.